2013
DOI: 10.3168/jds.2012-5723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing soybean meal protein with protein from upland cottonseed, Pima cottonseed, or extruded Pima cottonseed on production of lactating dairy cows

Abstract: Pima cotton production is increasing in the United States, but Pima cottonseed generally contains higher concentrations of the antinutritive pigment gossypol than conventional upland cottonseed. Heating promotes the reaction of gossypol with protein, reducing gossypol absorption and toxicity. The objective of this study was to assess the nutritional value for dairy cattle of Pima cottonseed cake (PCSC) that was heated and oil largely removed by an experimental extrusion process, compared with upland cottonseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…At a minimum, these data imply the water soluble fractions of cottonseed meal are comparable to the whole meals regarding protein nutrient. In other words, these soluble fractions of cottonseed and soy meal can still be used as dairy cow protein supplement as the original CSM [6]. …”
Section: Resultsmentioning
confidence: 99%
“…At a minimum, these data imply the water soluble fractions of cottonseed meal are comparable to the whole meals regarding protein nutrient. In other words, these soluble fractions of cottonseed and soy meal can still be used as dairy cow protein supplement as the original CSM [6]. …”
Section: Resultsmentioning
confidence: 99%
“…During the extrusion process, the high temperature, high pressure, and strong shear force change the physical properties of the feed, gelatinizing starch, denaturing proteins (Singh, Gamlath & Wakeling ), and destroying the anti‐nutrition factors present in soybean meal and cotton seed meal, such as trypsin inhibitors (Romarheim, Skrede, Gao, Krogdahl, Denstadli, Lilleeng & Storebakken ; Frederic, David & Hardy ) and gossypol (Broderick, Kerkman, Sullivan, Dowd & Funk ). Many studies have demonstrated that the digestion and absorption can be improved by extrusion (Maenz, Irish & Classen ; Francis, Makkar & Becker ; Drew, Borgeson & Thiessen ; Adamidou, Nengas, Henry, Grigorakis, Rigos, Nikolopoulou, Kotzamanis, Bell & Jauncey ; Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to fiber, cotton crop also produce a great amount of seed biomass (Bellaloui et al, 2015a;Pettigrew & Dowd, 2014). The residual fraction of cottonseed after oil crushing, called defatted cottonseed meal (CSM), is mainly used as soil amendment and animal feed (Broderick et al, 2013;Li et al, 2012;Wanapat et al, 2013). Thus, value added utilization of CSM products as industrial and biobased raw materials would increase the profitability of cotton growers and processors.…”
Section: Introductionmentioning
confidence: 99%